Landscape ecological pecularities of rodent helminths of mountainous and foothill territories of Lankaran natural region of Azerbaijan - Fataliyev, Gara Huseyn; Aslanova, Elnura Kamil (Experimental Biology and Biotechnology, 2019)
The information about the helminthfauna of mouse and landscape-ecological pecularities of mountainous and foothill territories of Lankaran natural region is represented in the article for the first time. As a result of investigation 38 species of helminths have been revealed: 8 thrematods, 14 sestods, 15 nematods and 1 akantotsefal. From revealed helminths 28 species are biohelminths and 10 species geohelminths. 9 spesies have something common with the manʼs and domestic animalʼs helminths.
Keywords: rodents; helminthfauna; landscape; biohelmint; geohelminth; biotic factors; abiotic factors